Technical report: detection of heart disease using Fuzzy Logic / Nur Shafeeza Azman, Nur Izzatul Balqis Rohaimin and Nurulain Nabilah Nor Azman - Azman, Nur Shafeeza; Rohaimin, Nur Izzatul Balqis; Nor Azman, Nurulain Nabilah (2017)
Nowadays, the detection of heart disease is quite complicated since it can be caused by many factors. However in this modern area, the use of computer technology and mathematical theory could help this process become easier. Therefore, in this study fuzzy logic system is developed to detect the heart disease. This fuzzy logic system consists four main components which is the fuzzy inference engine, fuzzy rule base, fuzzifier and defuzzifier. The system has been tested for 30 patients from Klinik Kesihatan Machang, Kelantan. This system consists 5 inputs field and 1 output field. From these inputs the fuzzy rule system are generated. Next fuzzification process using triangular and trapezoidal membership function was implied. Then, defuzzification process was perform to generate the output. The integer value lies from O to 1 and the number indicates from low to high. Hence, this study provide enrichment to the explanation of fuzzy logic through comparison of difference membership function in describing the similar output.